How does urbanization evolve heterogeneously in urbanized, urbanizing, and rural areas of China? Insights from ecosystem service value - Zhang, Yikun; Wang, Yongsheng (Geography and sustainability, 2025)
•Multi-source data was adopted to identify China's urbanized, urbanizing, and rural areas.•Urbanization positively impacted ESV, especially in more urbanized areas.•The urbanizing areas witnessed the most vibrant ESV changes.•Cultural services value in less urbanized areas has begun to surge since 2015. The rapid population and land urbanization not only promoted economic development but also affected the ecosystem service value (ESV). In the context of new-type urbanization and green development, it’s essential to investigate the impacts of urbanization on ESV in China. However, a comprehensive and dynamic framework to reveal the relationship between ESV and urbanization processes is lacking. This study adopted multi-source datasets to portray China’s urbanization process by integrating population, land, and economic urbanization, evaluated the ESV changes of 10 categories by gross ecosystem product (GEP) methods, and explored ESV changes within different urbanization scales and speeds. The results showed rapid urbanization in the population, land, and economic dimensions in China, with a faster process of economic urbanization. The ESV also exhibited an increasing trend, with higher levels in the southeastern coastal regions and lower levels in the northwestern regions. Urbanization had positive impacts on ESV across various research units, but the ESV exhibited heterogeneous changes across different urbanization scales, speeds, and their interactive effects. The response of ESV to dynamic urbanization processes was influenced by socio-economic, ecological, and policy factors; it is essential to combine targeted measures with general ecological product value realization methods in each unit to maximize social-economic-ecological benefits. [Display omitted]